The Implementation of Unplugged Coding Hijaiyah to Improve the Computational Skills of Children Aged 5–6 Years in the Era of KKA - Rofi’ah, Ulya Ainur; Salamah, Ummidlatus; Tining, Tining (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
This study aims to analyze the effectiveness of implementing Unplugged Coding Hijaiyah worksheets in improving computational skills among children aged 5–6 years at PAUDQ Nurfadlillah Tuban, particularly within the context of the KKA Era (Coding and Artificial Intelligence). This research employed a Classroom Action Research (PTK) design conducted in three phases: pre-cycle, Cycle I, and Cycle II. Research instruments consisted of structured observations, computational skill assessment sheets, and documentation of children’s learning activities. The pre-cycle findings indicated that children’s computational skills were still low, as evidenced by difficulties in sequencing, recognizing patterns, and completing tasks based on logic and problem-solving. In Cycle I, after the gradual introduction of the Unplugged Coding Hijaiyah worksheets, improvements were observed in logical and algorithmic thinking through manipulative activities supported by teacher scaffolding. The most significant improvement occurred in Cycle II, when worksheets were applied independently and collaboratively, enabling children to arrange complex Hijaiyah letter patterns, predict solutions, evaluate their steps, and work effectively in groups. In addition to promoting computational skills, the learning process strengthened religious literacy and spiritual values through the integration of Hijaiyah letters into cognitive activities. These findings confirm that the Unplugged Coding Hijaiyah worksheet represents an innovative and effective learning strategy to prepare young learners for the rapid development of digital technology while supporting the formation of Islamic character. This model is recommended as an alternative instructional approach in early childhood education to develop higher-order thinking skills from an early age in a holistic and contextual manner.